Supply chain optimization and GHG emissions in biofuel production from forestry residues in Sweden. (August 2022) - Basile, Flavia; Pilotti, Lorenzo; Ugolini, Marco; Lozza, Giovanni; Manzolini, Giampaolo
Abstract: This paper applies an innovative optimization methodology to the supply chain of biomethanol production starting from forestry residues in Sweden. The model accounts for the collection of the biomass, the transport to the biorefinery including intermediate storages and the biodiesel plant. Particular attention is devoted to the characterization from economic and environmental point of view of the transport by truck and trains, the impact of the drying process as well as the size of the biorefinery plant. Results show that the forestry residues collection is limited by the size of the biodiesel plants. The calculated cost of the fuel is around 525 €/t being the biorefinery the major cost. The equivalent CO2 emissions are around 10.4 gCO2 /MJMeOH thanks to the low carbon intensity of the Swedish electricity. A sensitivity analysis showed that the supply chain does not vary significantly assuming higher prices of biomethanol.